PENETAPAN GANTI RUGI HAK ATAS TANAH BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Fajrian Noor Anugrah (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
This research aims to examine concerning the determination of the compensationland rights based on law No. 2 Of 2012 about the procurement of land fordevelopment for the public interest, namely the determination of the form andProcedure examines the value of compensation for land rights in the provision ofland and the concept of the public interest in the provision of land for theimplementation of the construction according to the law. Research conducted isnormative legal research that seeks to discover the principles of law that are notmet in the form of the assignment procedure and the value of compensation forland rights and the concept of the public interest in the procurement of landprovided for in Act No. 2 Of 2012. Determination of the procedures andarrangements the value soil procurement damages for execution of developmentwhich are regulated by Act No. 2 of 2012 more clearly than the determination ofthe procedure and the value of the land procurement damages provided for in theprevious Legislation. In the Act is regulated with a clear period of implementationof the procurement of land at each stage, both stages of the planning, thepreparation stage, the stage of implementation, up to submission of results. Basedon the results of the study showed that in law number 2 of 2012 setimplementation of the deliberations that are part of the assignment procedure andthe value of damages was conducted in order to establish the form and/or theamount of damages based on the results of the assessment of damages made bythe evaluator. From those settings do not meet the basic agreement that Statesthat the deliberations conducted by the parties without the element of coercion toget a deal together.While the concept of public interest mentioned by Act No. 2 of2012 that construction used for the prosperity of most people, providingopportunities for a handful of people to utilize the development results to enrichyourself.